Makna Metafora Idiom (Kanyouku) dalam Unsur Mata (ME): Sebuah Kajian Linguistik Kognitif - Teguh Santoso; Rosalina Wahyu Riani (Universitas Muhammadiyah Yogyakarta, 2019)
Idioms are an odd form of expression of a language; an expression whose meaning cannot be revealed from its true meaning; odd language generated by language users; language variation; dialect; Individual terminology from the rules about the expression characteristics of a group, profession, and the like. This research uses descriptive-qualitative research methods. The data in this study obtained through library techniques with data sources are texts which contain the meaning of the eye idiom (me). In the study of cognitive linguistics, linguistic analysis generally begins with the analysis of meaning. Kanyouku (me) is classified into five, namely kanyouku which shows feelings, emotions, idioms that relate to body, character, and attitude, kanyouku that indicate actions, actions, or activities, kanyouku that indicate a state, degree, or level of value, and kanyouku that show local life, culture and society. From the findings, there are 8 data that correlated in this case.